Strategi Marketing di Instagram @MichiePudding dalam Meningkatkan Penjualan - Suhatta, Alfredo; Haryono, Cosmas Gatot (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The increasingly competitive landscape of Micro, Small, and Medium Enterprises (MSMEs), particularly in the food sector, requires businesses to develop innovative marketing approaches to remain competitive. In the digital era, social media especially Instagram plays a vital role in enhancing product visibility through visually appealing content. This study aims to explore the social media marketing content strategy implemented by the @MichiePudding brand in promoting its pudding products. The research employs a qualitative method, using content analysis of Instagram posts and in-depth interviews with key informants including the business owner of @MichiePudding, several customers, and social media specialists. The findings indicate that effective strategies involve regular posting, maintaining aesthetic consistency in product presentation, engaging storytelling, and strategic advertising campaigns. Additionally, the brand's focus on packaging design and visual identity contributes significantly to customer attraction and retention. The research concludes that a well-structured and visually driven Instagram strategy can positively influence sales performance and brand recognition. These insights offer practical recommendations for other MSMEs seeking to optimize their social media presence and adapt to the dynamic digital marketing environment.